Ireland and the Popish Plot - Gibney, John. author. aut Link
X, 206 p.
Keywords: The first expansive study of how when the Popish Plot of 1678 came to light, fears of an Irish Catholic rebellion amongst Ireland's uneasy Protestant elite, who dominated over the Catholic majority population, were manipulated in England in an attempt to block the Catholic Duke of York from succeeding to the throne.